Giving Meaning to Numbers and Operations in Arithmetic - Subramaniam, K. (Voices of Teachers and Teacher Educators, 2016)
This article discusses with examples how basic abstract structures of Mathematics can be taught with examples from real life situations. The author gives examples of contexts that can be used basic for operations of Mathematics. This article explores foundational concepts in arithmetic by examining how meaning is assigned to numbers and operations, aiming to bridge intuitive understanding and formal mathematical knowledge. The author discusses strategies to help learners connect symbolic representations with real-world quantities, which is crucial for developing strong number sense and arithmetic skills. Key approaches include the use of concrete manipulatives, visual models, and real-life contexts to illustrate addition, subtraction, multiplication, and division, helping learners grasp the functional relationships between numbers. Additionally, the article considers cognitive processes behind numerical comprehension and addresses common misconceptions. By emphasizing a conceptual understanding of numbers and operations, the article advocates for instructional practices that foster deeper, more flexible mathematical thinking among students.